(untitled) (HIMALAYA, 2025)
Nepal and surrounding regions in India are known for resplendent masked performances. Often ritual in nature, they serve as tools for spiritual belonging, community cohesion, ties of kinship, and artistic expression. Research on Nepal’s culture and performance traditions has been smaller compared to neighboring South Asian countries such as India, Bangladesh and Sri Lanka. Nepal’s performance traditions are complex, with centuries of history, culture, and religious beliefs attached to them. In Nepal, many of these traditional performances are called Pyakhan or stories/parables. They are deserving of in-depth study, much like their other South Asian counterparts. This paper takes a deep dive into masked dance forms of Nepal, especially the making and use of masks in Bhairab Nach, and Navadurga performance.